A wear-resistant light-cured dental composite resin material and preparation method thereof

By combining modified inorganic fillers and organic monomers, a dental composite resin material with core-shell structure is solved, and the wear resistance and service life of the existing materials are significantly improved.

CN116035918BActive Publication Date: 2025-03-14UNIV OF SHANGHAI FOR SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211631991.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2025-03-14
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

Under the long-term service conditions, existing dental composite resin materials have problems such as poor bonding with the teeth and poor wear resistance.

Method used

Using modified inorganic fillers, by mixing SiO2 and h-BN with anhydrous ethanol and reacting under the action of a surface modifier, surface modified inorganic fillers are formed, combined with organic monomers and photoinitiators, premixed under light-proof conditions and photocured to form a dental composite resin material with a core-shell structure.

Benefits of technology

It improves the lubricating performance and wear resistance of dental composite resin materials and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116035918B_ABST
    Figure CN116035918B_ABST
Patent Text Reader

Abstract

The present invention provides a wear-resistant light-cured dental composite resin material and a preparation method thereof, wherein the raw materials of the composite resin include a surface-modified inorganic filler, an organic monomer and a photoinitiator. The inorganic filler is SiO2 and h-BN, and the total content is 7.8-9.2wt%. The preparation method comprises the steps of surface-modifying the inorganic filler with a silane coupling agent; then uniformly mixing the modified inorganic filler with an organic monomer and a photoinitiator under light-proof conditions to obtain an uncured composite resin; and finally, photocuring to obtain a dental composite resin. The present invention achieves an improvement in the wear resistance of the dental composite resin material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of dental restoration materials, and in particular relates to a wear-resistant light-cured dental composite resin and a preparation method thereof. Background Art

[0002] Data shows that about 200 million people in the world need oral rehabilitation every year. Among them, tooth wear is one of the main difficult cases encountered in the clinical diagnosis and treatment of oral rehabilitation. It is a common clinical non-carious disease of tooth hard tissue. It refers to the progressive loss of tooth hard tissue caused by mechanical friction or chemical acid erosion. According to surveys, tooth wear is closely related to people's age and eating habits. With age or the intake of acidic foods, the wear of the functional surfaces of teeth will gradually increase. The loss of tooth hard tissue caused by tooth wear is irreversible. Tooth wear can be accompanied by a variety of complications or become the cause of certain diseases. For example, it often causes symptoms such as toothache, food impaction, and difficulty chewing. For patients with severe complications, complex root canal treatment, crown or high onlay restoration are often required. Those with more severe wear even require complex occlusal reconstruction treatment. Therefore, slowing down tooth wear has important clinical value in reducing oral diseases and oral rehabilitation.

[0003] In recent years, light-cured dental composite resin is a commonly used material for oral restoration. It is a composite composed of organic monomers, photoinitiators, and inorganic fillers. The commonly used organic monomers and inorganic fillers in commercial dental composite resin materials are dimethacrylates and silica, respectively. They have the advantages of chemical stability, insolubility in saliva, and good mechanical strength. However, under long-term service conditions, this composite resin material still faces problems such as poor bonding between the composite resin material and the tooth body and poor wear resistance. Therefore, how to improve the wear resistance of dental composite resin is the key to the development and application of this technology.

[0004] At present, there are three main methods to improve the wear resistance of dental composite resins: first, surface modification of inorganic fillers to improve their dispersibility in organic reagents, thereby improving the wear resistance of the material; second, regulation of the content, morphology, particle size and particle size distribution of inorganic fillers; and third, addition of a diversified combination of inorganic fillers. However, the inorganic fillers selected above are mainly hard fillers. Although they have a certain contribution to improving mechanical properties and wear resistance, when hard inorganic fillers are on the surface of the resin matrix, they may also increase the degree of wear due to abrasive wear, thereby limiting the service life of the composite resin material. Summary of the invention

[0005] In view of the defects of the prior art, the object of the present invention is to provide a wear-resistant light-cured dental composite resin material and a preparation method thereof.

[0006] In one aspect, the present invention provides a wear-resistant light-cured dental composite resin material, the composite resin material is composed of a modified inorganic filler, an organic monomer and a photoinitiator, wherein the modified inorganic filler is an inorganic filler SiO 2 The surface-modified inorganic filler is obtained by mixing hexagonal boron nitride (h-BN) with anhydrous ethanol and reacting with a surface modifier.

[0007] Furthermore, the surface modifier is a silane coupling agent (KH570), KH570 and the inorganic filler SiO 2 The mass ratio of H-BN to h-BN is 0.01 to 0.02:1.

[0008] Furthermore, in the inorganic filler, SiO 2 The mass ratio of H-BN to h-BN is 10 to 0.25:1.

[0009] Furthermore, relative to the total weight of the composite resin material, the organic monomer accounts for 90-91 wt %, the photoinitiator accounts for 0.8-1.2 wt %, and the modified inorganic filler accounts for 7.8-9.2 wt %.

[0010] Furthermore, the organic monomer is composed of bisphenol A-glycidyl methacrylate (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA), and preferably, the mass ratio of Bis-GMA to TEGDMA is 0.5 to 1:1.

[0011] Furthermore, the photoinitiator is composed of camphorquinone (CQ) and dimethylaminoethyl methacrylate (DMAEMA), and preferably, the mass ratio of CQ to DMAEMA is 1 to 1.5:4.

[0012] Furthermore, the wear-resistant light-curing dental composite resin material presents a core-shell structure.

[0013] In another aspect, the present invention provides a method for preparing the above-mentioned wear-resistant light-cured dental composite resin material, the preparation method comprising the following steps:

[0014] (1) Surface modification of inorganic fillers: nano h-BN, SiO 2 and anhydrous ethanol under ultrasound to obtain a mixed solution, slowly adding the KH570 solution diluted with anhydrous ethanol to the mixed solution, heating to 55-60° C. under stirring to react, and after the reaction is completed, vacuum drying the reaction solution to obtain a modified inorganic filler;

[0015] (2) Preparation of composite resin material: premixing the modified inorganic filler, organic monomer and photoinitiator under light-proof conditions, and curing with visible ultraviolet light to obtain the wear-resistant light-cured dental composite resin material.

[0016] Preferably, in the inorganic filler, the particle size of h-BN is 0-1 μm, and the particle size of SiO 2 The particle size is 0~35nm.

[0017] Preferably, in step (1), the mass ratio of the inorganic filler to anhydrous ethanol is 1:25-50.

[0018] Preferably, the surface modifier of the inorganic filler is silane coupling agent KH570, and the mass ratio of KH570 to the inorganic filler is 0.01-0.02:1.

[0019] Preferably, in step (1), in the KH570 solution diluted with anhydrous ethanol, the mass ratio of anhydrous ethanol to KH570 is 99 to 90:1.

[0020] Preferably, in step (1), the ultrasonic mixing time is 30 to 60 min, the stirring speed is 300 to 400 rpm, the stirring time is 2 to 2.5 h, and the vacuum drying time is 4 to 5 h.

[0021] Preferably, in step (2), the ultraviolet light wavelength range is 460 to 480 nm, and the curing time is 20 to 30 s.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The light-cured dental composite resin material of the present invention contains inorganic fillers in addition to SiO 2 , and h-BN, but there is no report on adding h-BN to inorganic fillers in light-cured dental composite resins. The addition of h-BN, on the one hand, relies on the weak shearing effect between its layered structures, and on the other hand, it interacts with SiO 2 The synergistic effect forms a core-shell structure, which can improve the lubrication properties of dental composite resin materials and thus enhance their wear resistance.

[0024] The method for preparing the light-cured dental composite resin material of the present invention comprises: 2 , h-BN and anhydrous ethanol are ultrasonically dispersed and alkylated to form a modified core-shell structure. The surface-modified inorganic filler, organic monomer and photoinitiator are pre-mixed and photocured under light-proof conditions to obtain a dental composite resin material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 FTIR spectra of the surface-modified inorganic fillers in Examples 1-5 of the present invention;

[0026] Figure 2 is the friction coefficient curve of the composite resin in Examples 1-5 of the present invention;

[0027] Figure 3 It is the wear rate of the composite resin in Examples 1-5 of the present invention after 24,000 wear tests. DETAILED DESCRIPTION

[0028] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, without departing from the concept of the present invention, several changes and improvements can also be made, which all belong to the protection scope of the present invention.

[0029] Example 1

[0030] This embodiment provides a wear-resistant light-cured dental composite resin material and a preparation method, which is specifically implemented as follows:

[0031] Surface modification of inorganic fillers

[0032] Take inorganic filler SiO 2 and h-BN, a total of 1.1 g, with a mass ratio of 10:1, of which SiO 2 The particle size of is 30±5nm, the purity is 99.5%, and the particle size of h-BN is 1μm, the purity is 98.5%. Then 27.5ml of anhydrous ethanol is added, and ultrasonic mixing is performed for 30min; then a mixed solution of KH570 and anhydrous ethanol with a mass ratio of 1:99 is slowly added to the above ultrasonic mixed solution, and magnetic stirring is performed for 2h, the stirring speed is 400rpm, and the heating temperature is 55-60℃; finally, the obtained solution is vacuum dried for 4h to obtain a modified inorganic filler.

[0033] Preparation of light-cured dental composite resin materials

[0034] Take 3.33 g of bisphenol A-glycidyl methacrylate Bis-GMA, triethylene glycol dimethacrylate TEGDMA, camphorquinone CQ, dimethylaminoethyl methacrylate DMAEMA and modified inorganic filler, the content of each component is shown in Table 1, and the above materials are premixed under light-proof conditions to obtain an uncured composite resin, and finally cured with visible ultraviolet light (460-480 nm) for 20 to 30 seconds to obtain a dental composite resin.

[0035] Table 1 Components of dental composite resin and the content of each component

[0036]

[0037] Characterization of wear resistance of composite resins

[0038] The wear resistance of the composite resin was evaluated by a ball-disk reciprocating sliding friction and wear tester. The positive load was 30N, the sliding frequency was 100rpm, the sliding time was 2h, the total number of sliding wear was 24000 times, the average friction coefficient was 0.91±0.09, the wear mass was 1.2±0.4mg, the wear depth was about 175μm, and the wear rate was (3.36±0.07)×10 - 4 mm 3 / (N·mm).

[0039] Example 2

[0040] This embodiment provides a wear-resistant light-cured dental composite resin material and a preparation method, which is specifically implemented as follows:

[0041] (1) Surface modification of inorganic fillers

[0042] Take inorganic filler SiO 2 and h-BN, a total of 1.8 g, with a mass ratio of 8:1, of which SiO 2 The particle size of 30±5nm, purity 99.5%, the particle size of h-BN is 1μm, purity 98.5%. Then add 45ml of anhydrous ethanol to the inorganic filler and perform ultrasonic mixing for 30min; then slowly add a mixed solution of KH570 and anhydrous ethanol with a mass ratio of 1:99 to the above-mentioned ultrasonic mixed solution, magnetically stir for 2h, the stirring speed is 400rpm, and the heating temperature is 55-60℃; finally, the obtained solution is vacuum dried for 4h to obtain the modified inorganic filler.

[0043] (2) Preparation of light-cured dental composite resin materials

[0044] The raw material components and preparation method of the dental composite resin prepared in this embodiment 2 are the same as those in embodiment 1, except that the modified inorganic filler obtained in step (1) of this embodiment 2 is added.

[0045] (3) Characterization of wear resistance of composite resin

[0046] The wear resistance of the composite resin prepared in Example 2 was characterized by the same method as that in Example 1. The average friction coefficient of the composite resin was 1.02±0.11, the wear mass was 1.8±0.2 mg, the wear depth was about 187 μm, and the wear rate was (3.76±0.17)×10 -4 mm 3 / (N·mm).

[0047] Example 3

[0048] This embodiment provides a wear-resistant light-cured dental composite resin material and a preparation method, which is specifically implemented as follows:

[0049] (1) Surface modification of inorganic fillers

[0050] Take inorganic filler SiO 2 and h-BN, a total of 1.4 g, with a mass ratio of 6:1, of which SiO 2 The particle size of 30±5nm, purity 99.5%, the particle size of h-BN is 1μm, purity 98.5%. Then add 35ml of anhydrous ethanol to the inorganic filler and perform ultrasonic mixing for 30min; then slowly add a mixed solution of KH570 and anhydrous ethanol with a mass ratio of 1:99 to the above ultrasonic mixed solution, magnetically stir for 2h, the stirring speed is 400rpm, and the heating temperature is 55-60℃; finally, the obtained solution is vacuum dried for 4h to obtain the modified inorganic filler.

[0051] (2) Preparation of light-cured dental composite resin materials

[0052] The raw material components and preparation method of the dental composite resin prepared in this embodiment 3 are the same as those in embodiment 1, except that the modified inorganic filler obtained in step (1) of this embodiment 3 is added.

[0053] (3) Characterization of wear resistance of composite resin

[0054] The wear resistance of the composite resin prepared in Example 3 was characterized by the same method as that in Example 1. The average friction coefficient of the composite resin was 0.99±0.09, the wear mass was 0.9±0.3 mg, the wear depth was about 145 μm, and the wear rate was (2.38±0.24)×10 -4 mm 3 / (N·mm).

[0055] Example 4

[0056] This embodiment provides a wear-resistant light-cured dental composite resin material and a preparation method, which is specifically implemented as follows:

[0057] (1) Surface modification of inorganic fillers

[0058] Take inorganic filler SiO 2 and h-BN, a total of 1.5 g, with a mass ratio of 4:1, of which SiO 2The particle size of 30±5nm, purity 99.5%, the particle size of h-BN is 1μm, purity 98.5%. Then add 37.5ml of anhydrous ethanol to the inorganic filler and perform ultrasonic mixing for 30min; then slowly add a mixed solution of KH570 and anhydrous ethanol with a mass ratio of 1:99 to the above ultrasonic mixed solution, magnetically stir for 2h, the stirring speed is 400rpm, and the heating temperature is 55-60℃; finally, vacuum dry the obtained solution for 4h to obtain the modified inorganic filler.

[0059] (2) Preparation of light-cured dental composite resin materials

[0060] The raw material components and preparation method of the dental composite resin prepared in this embodiment 4 are the same as those in embodiment 1, except that the modified inorganic filler obtained in step (1) of this embodiment 4 is added.

[0061] (3) Characterization of wear resistance of composite resin

[0062] The wear resistance of the composite resin prepared in Example 4 was characterized by the same method as that in Example 1. The average friction coefficient of the composite resin was 0.97±0.07, the wear mass was 0.9±0.2 mg, the wear depth was about 134 μm, and the wear rate was (2.20±0.34)×10 -4 mm 3 / (N·mm).

[0063] Example 5

[0064] This embodiment provides a wear-resistant light-cured dental composite resin material and a preparation method, which is specifically implemented as follows:

[0065] (1) Surface modification of inorganic fillers

[0066] Take inorganic filler SiO 2 and h-BN, a total of 1.5 g, with a mass ratio of 2:1, of which SiO 2 The particle size of 30±5nm, purity 99.5%, the particle size of h-BN is 1μm, purity 98.5%. Then add 37.5ml of anhydrous ethanol to the inorganic filler and perform ultrasonic mixing for 30min; then slowly add a mixed solution of KH570 and anhydrous ethanol with a mass ratio of 1:99 to the above ultrasonic mixed solution, magnetically stir for 2h, the stirring speed is 400rpm, and the heating temperature is 55-60℃; finally, vacuum dry the obtained solution for 4h to obtain the modified inorganic filler.

[0067] (2) Preparation of light-cured dental composite resin materials

[0068] The raw material components and preparation method of the dental composite resin prepared in this Example 5 are the same as those in Example 1, except that the modified inorganic filler obtained in step (1) of this Example 5 is added.

[0069] (3) Characterization of wear resistance of composite resin

[0070] The wear resistance of the composite resin prepared in Example 5 was characterized by the same method as that in Example 1. The average friction coefficient of the composite resin was 0.81±0.09, the wear mass was 0.6±0.2 mg, the wear depth was about 120 μm, and the wear rate was (1.83±0.16)×10 -4 mm 3 / (N·mm).

[0071] Figure 1 The FTIR spectra of the surface-modified inorganic fillers in Examples 1-5 of the present invention are shown. Figure 1 It can be seen that 2987cm -1 The nearby peak is -CH 3 and -CH 2 The stretching vibration absorption peak of SiO 2 With the increase of mass ratio of -CH 3 and -CH 2 The intensity of the stretching vibration absorption peak increases, which indicates that the higher the organic content of the inorganic filler, the better the surface modification.

[0072] Figure 2 and Figure 3 The friction coefficient curves of the composite resins in Examples 1-5 of the present invention and the wear rates after 24,000 wear tests are shown respectively. Figure 2 and Figure 3 It can be seen that the composite resin prepared in Example 5 has the smallest average friction coefficient and the lowest wear rate, showing the best wear resistance.

[0073] Comparative Example 1

[0074] This comparative example provides a wear-resistant light-cured dental composite resin material and a preparation method thereof. Compared with Example 1, no h-BN inorganic filler is added, and other processes are the same.

[0075] Compared with Example 1, the average friction coefficient and wear rate of the composite resin increased.

[0076] Comparative Example 2

[0077] This comparative example provides a wear-resistant light-cured dental composite resin material and a preparation method. Compared with Example 1, the size of the added inorganic filler h-BN is adjusted to 2-4 μm, and other processes are the same.

[0078] Compared with Example 1, the average friction coefficient of the composite resin is comparable, but the wear rate is increased.

[0079] Comparative Example 3

[0080] This comparative example provides a wear-resistant light-cured dental composite resin material and a preparation method. Compared with Example 1, the added inorganic filler SiO 2 The size is adjusted to 40-100nm, and the other processes are the same.

[0081] Compared with Example 1, the average friction coefficient of the composite resin is comparable, but the wear rate is increased.

[0082] Comparative Example 4

[0083] This comparative example provides a wear-resistant light-cured dental composite resin material and a preparation method. Compared with Example 1, the mass ratio of the added surface modifier KH570 to the inorganic filler is less than 0.02, and other processes are the same.

[0084] Compared with Example 1, the surface alkylation of the inorganic filler is difficult to achieve.

[0085] Comparative Example 5

[0086] This comparative example provides a wear-resistant light-cured dental composite resin material and a preparation method thereof. Compared with Example 1, the magnetic stirring temperature is higher than 70° C., and other processes are the same.

[0087] Compared with the inorganic filler modification process in Example 1, ethanol will evaporate quickly and the surface alkylation of the inorganic filler is difficult to achieve.

[0088] Comparative Example 6

[0089] This comparative example provides a wear-resistant light-cured dental composite resin material and a preparation method. Compared with Example 1, the mass ratio of Bis-GMA to TEGDMA is 2:1, and other processes are the same.

[0090] Compared with Example 1, the viscosity of the composite resin is too high and it is difficult to mix evenly.

[0091] Comparative Example 7

[0092] This comparative example provides a wear-resistant light-cured dental composite resin material and a preparation method. Compared with Example 1, the mass ratio of CQ to DMAEMA is 1:8, and other processes are the same.

[0093] Compared with Example 1, the composite resin curing time is longer.

[0094] Comparative Example 8

[0095] This comparative example provides a wear-resistant light-cured dental composite resin material and a preparation method. Compared with Example 1, the inorganic filler SiO2 The mass of h-BN accounts for 15wt% of the total mass of the dental composite resin, and the other processes are the same.

[0096] Compared with Example 1, the average friction coefficient and wear rate of the composite resin increased.

[0097] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A wear-resistant light-cured dental composite resin material, the composite resin material is composed of a modified inorganic filler, an organic monomer and a photoinitiator, wherein: The modified inorganic filler is a surface-modified inorganic filler obtained by mixing inorganic filler SiO2 and hexagonal boron nitride h-BN with anhydrous ethanol and reacting them under the action of a surface modifier; Relative to the total mass of the composite resin material, the organic monomer accounts for 90-91wt%, the photoinitiator accounts for 0.8-1.2wt%, and the modified inorganic filler accounts for 7.8-9.2wt%; the h-BN has a layered structure; the surface modifier is a silane coupling agent KH570, and the mass ratio of KH570 to the inorganic filler SiO2 and h-BN is 0.02:1; the particle size of the h-BN is 1μm, and the particle size of the SiO2 is 30±5nm; The organic monomer is composed of bisphenol A-glycidyl methacrylate (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA), and the mass ratio of Bis-GMA to TEGDMA is 0.5 to 1:1; The photoinitiator consists of camphorquinone (CQ) and dimethylaminoethyl methacrylate (DMAEMA), and the mass ratio of CQ to DMAEMA is 1 to 1.5:

4.

2. The wear-resistant light-cured dental composite resin material according to claim 1, characterized in that: In the inorganic filler, the mass ratio of SiO2 to h-BN is 10 to 0.25:

1.

3. The method for preparing the wear-resistant light-cured dental composite resin material according to any one of claims 1 to 2, comprising the following steps: (1) Surface modification of the inorganic filler: h-BN, SiO2 and anhydrous ethanol are mixed under ultrasound to obtain a mixed solution, a KH570 solution diluted with anhydrous ethanol is slowly added to the mixed solution, and the mixture is heated to 55-60° C. under stirring to react. After the reaction is completed, the reaction solution is vacuum dried to obtain a modified inorganic filler; (2) Preparation of composite resin material: premixing the modified inorganic filler, organic monomer and photoinitiator under light-proof conditions, and curing with visible ultraviolet light to obtain the wear-resistant light-cured dental composite resin material.

4. The preparation method according to claim 3, characterized in that: In step (1), the mass ratio of the inorganic filler to anhydrous ethanol is 1:25-50.

5. The preparation method according to claim 3, characterized in that: In step (1), the ultrasonic mixing time is 30 to 60 minutes, the stirring speed is 300 to 400 rpm, the stirring time is 2 to 2.5 hours, and the vacuum drying time is 4 to 5 hours.

6. The preparation method according to claim 3, characterized in that: In step (2), the wavelength range of ultraviolet light is 460 to 480 nm, and the curing time is 20 to 30 seconds.

Citation Information

Patent Citations

  • Preparation method of dentistry composite resin material capable of improving abrasion resistance and obdurability

    CN101507687A

  • Nano SiO2 coated BN composite powder, preparation method thereof and thermal conductive material

    CN111534287A

  • Hybrid boron nitride-nano silicon dioxide modified phthalazinone polyarylether resin-based composite material and preparation method thereof

    CN116694078A